The Use of Matching Picture to Enrich Vocabulary Mastery of the Kindergarten Students - Dyah Kartika Sari; J. Priyanto Widodo; Lailatul Musyarofah (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study aimed to know how using matching picture game as a strategy in learning vocabulary for young learners can increase students' vocabulary mastery at TK Kristen Petra 12 Sidoarjo in the academic year 2020/2021. The study took four weeks. During the Covid-19 pandemic, an online class met twice a week for 30 minutes each. Between April 3rd and April 28th, 2021, 8 sessions were held to investigate. The research subjects were TK Kristen Petra 12 Sidoarjo of the class B2 consisting 22 children. The researcher and the field note were the instruments. The tests were used to collect data before the study and after the picture game implemented. Before the Picture Game treatment, the students’ performance was below average. 2.71 was the mean. The children’ language mastery vocabulary was limited. The implementation of Picture Game increased the mean score to 3.62. The students used effective approach to obtain accurate results and logical reasoning to achieve their conclusion.